KARAKTERISTIK KIMIA DAN ORGANOLEPTIK JELLY DRINK FILTRAT DAUN KELOR YANG DITAMBAHKAN GELATIN - Bernard, Rianty; Lopulalan, Cynthia G. Christina; Picauly, Prisylia (MARSEGU : Jurnal Sains dan Teknologi, 2024)
Tropical plants that have health benefits are moringa plants. Moringa is currently the most widely consumed food. The aim of this study was to analyze the chemical and organoleptic characteristics of moringa leaf extract jelly drinks processed with gelatin concentrate. The design used was a Randomized Design (CRD) with gelatin concentration treatments of 30, 40 and 50%, 3 replications. The results obtained were that the higher the concentration of gelatin had a significant effect on fiber, vitamin C and dissolved solids content, and reduced water content. The results of the organoleptic test showed that the three treatments did not provide a significant effect between treatments.